2019
DOI: 10.1371/journal.pone.0220455
|View full text |Cite
|
Sign up to set email alerts
|

Positive attitudes, positive outcomes: The relationship between farmer attitudes, management behaviour and sheep welfare

Abstract: This study examined the relationships between the attitudes and the management behaviour of the farmer and the on-farm welfare of their ewes. To our knowledge, this is the first study investigating these relationships in extensive sheep farming systems. Thirty-two sheep farmers and 6200 ewes were sampled across Victoria, Australia. Questionnaire interviews and on-farm animal welfare assessments were conducted. The ewes were assessed at two-time points, mid-pregnancy and weaning. To examine relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 34 publications
4
30
2
1
Order By: Relevance
“…Therefore, the results suggest that the intention of pig farmers to construct pig housing increases if they have a positive attitude towards constructing a pen to improve animal welfare. This result is in line with previous studies showing that attitudes are one of the most influential factors determining the implementation decisions of public relations measures at the individual farm level [ 70 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the results suggest that the intention of pig farmers to construct pig housing increases if they have a positive attitude towards constructing a pen to improve animal welfare. This result is in line with previous studies showing that attitudes are one of the most influential factors determining the implementation decisions of public relations measures at the individual farm level [ 70 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 92%
“…Thus, if the intention to construct pig housing is high, this high intention will have a positive effect on actual building behavior. A significant influence of intention on behavior in agricultural decisions was also found in the studies of Ambrosius et al [ 75 ] and Munoz et al [ 71 ].…”
Section: Resultssupporting
confidence: 66%
“…This latter aspect highlights the lack of knowledge concerning the relationship between animal welfare and productivity and signals an oppoortunity for animal welfare improvement by targeting sheep farmers' attitude. In particular, Munoz et al (2019) observed a close relationship between farmer attitude and management decisions, which in turn were able to markedly affect the welfare of sheep kept for meat production. The attitude of farmers, even when they are not directly involved in farm activities and animal handling, has an impact on stock-people attitude and behaviour in terms of training provided and priorities identified in flock management.…”
Section: Humansmentioning
confidence: 99%
“…In a recent cross-cultural study, the quality of HAR was not mentioned by a number of stakeholders when asked to list the most important aspects to be considered to sustain sheep welfare (Dalla Costa et al, 2019) and, although incorporated in the AWIN scheme under the form of a familiar human approach test (AWIN, 2015), it was not included in a list of relevant parameters for the assessment of the welfare of sheep kept for meat production (Munoz et al, 2017). Accordingly, Phillips and Phillips (2010) noted that farmers consider long-lasting factors such as malnutrition, poor management and parasite infestations, as the main welfare issues in sheep kept for meat production in Australia, whereas animal welfare activists paid more attention to acute pain induced by mutilations such as castration.…”
Section: Humansmentioning
confidence: 99%
“…Most One Welfare research to-date has focused on how the psychological and emotional well-being of farmers can affect sheep welfare, and particularly, neglectful care [10], or the effect of farmer attitudes and behavior on fear and stress behaviors associated with animal handling [11]. Indeed, recent work confirms that positive farmer attitudes to routine farm management tasks and enjoyment of working with sheep are associated with positive welfare outcomes for the sheep [12]. Conversely, in this study, we were interested in how a disease with severe negative consequences for sheep health and welfare, and specifically the outbreak of a new disease, could have impacted the emotional well-being of sheep farmers.…”
Section: Introductionmentioning
confidence: 99%